Morphology Performance On Six Black Rice Accessions (Oryza Sativa L.) In M1 Generation Irradiated By Gamma Rays - Jujun Widian; Siti Nurhidayah; Sherly Rahayu; Efrin Firmansyah; Roza Yunita (Department of Crop Science, Faculty of Agriculture, Andalas University, 2021)
Increasing the genetic diversity of plants can be done through physical mutations with gamma-ray irradiation. This study aims to determine gamma-ray irradiation on the growth of six M1 generation black rice accessions. This research was conducted in May-October 2019 at the Experimental Rice Fields of the Tasikmalaya Perjuangan University, West Java. The materials used in this study were six accessions from Tasikmalaya (PH, PH2, PH3, PH5, PH7, and PH8) without 0 Gy irradiation and with 200 Gy gamma-ray irradiation of M1 generation. The results showed that gamma-ray irradiation reduced germination characteristics, seedling height, and flowering age. Some of the accessions showed different effects; there were a decrease and an increase in the characters of root length, plant height, number of productive tillers, number of unproductive tillers, and the total number of tillers.